Reward, equity and conflict: a dynamic approach. (2nd November 2004) - Hunter, L.C.; McCormack, D.J.; Rimmer, R.J.
In the past, constant pay rates and piece-rate systems were applied to reward employee effort. Now pay adjustments may vary between employees on the basis of subjective judgements of performance. Consequently, employees may feel that they are unfairly treated. Conflict follows with managers or supervisors who are enforcing corporate goals on production, quality and cost containment. A theoretical framework is proposed within which to study interactions between employees and employers over effort. Four features are demonstrated. Firstly, management can simulate the effects of policy alternatives. Secondly, many theories can be analysed within the framework. A theory of conflict over pay is considered. Then, in effort-wage bargaining chaotic outcomes are demonstrated. Finally, even with such complex outcomes, conventional human resource strategies are shown to moderate the variability of employee responses when remuneration is considered inequitable.